IMPLEMENTASI HOTS DALAM PEMBELAJARAN FIQIH DAN IMPLIKASINYA TERHADAP NALAR HUKUM ISLAM SISWA MADRASAH ALIYAH - Amara Desinta; Alin Af Idah; Raihan Syafa Yunanto; Nur Zaidi Salim (CV. Bunda Ratu, 2026)
This study examined the implementation of Higher Order Thinking Skills-based Fiqh learning and its impact on students’ Islamic legal reasoning at Madrasah Aliyah. The study addressed the dominance of textual and memorization-oriented instruction that limited students’ critical engagement with legal sources. A qualitative descriptive approach was employed, involving two Fiqh teachers and twelve students selected purposively. Data were collected through in-depth interviews and document analysis, and analyzed using an interactive model of data reduction, display, and conclusion drawing. The findings showed that the implementation of problem-based and contextual learning encouraged students to actively analyze legal texts, evaluate diverse scholarly opinions, and construct reasoned conclusions. Students demonstrated a shift from passive reception of legal rules to critical, reflective, and argument-based understanding. Furthermore, the learning process contributed to the development of contextual and adaptive Islamic legal reasoning. This study concluded that Higher Order Thinking Skills-based Fiqh learning functioned not only as a pedagogical strategy but also as an epistemological approach that supported the formation of students’ analytical and contextual legal thinking.